About Future of Work and Future Without Work (Futurology Discussions) - Андрей Вячеславович Шевчук (Journal of Economic Sociology, 2010)
The paper is devoted to one of the aspects of the mass socio-economic transformation related to the post industrial society development and changes in the employment system. They are so radical that a number of futurologists questioned not simply about future of labour but about future without labour.